Faculty Members Perceptions of Open Access Publishing in Ghana - Buondau, Albert; Mensah Danquah, Monica; Dadzie, Perpetua S. (Ghana Library Journal, 2024)
This study sought to determine the rate of acceptance and use of open access scholarly resources by faculty members in Ghana. The study population was 443 faculty members. Using a survey design, a questionnaire was employed as the data collection instrument. Data collected were analyses using Statistical Package for Social Science (SPSS v20) and thematic analysis for qualitative data. Key findings were that although the faculty members showed positive attitudes towards open access publishing and had intentions to publish in open access journals and use open access content, they perceived that open access journals increase predatory journal publication, have poor impact factors, with murky peer review process. Recommendations based on study findings were thus directed towards the development of policies that promote open access publication, equipping libraries within the institutions with IT resources to develop and sustain open access journals, and increasing education on OAJs among others.